2020
DOI: 10.1038/s41467-020-16824-2
|View full text |Cite
|
Sign up to set email alerts
|

Surface regulation enables high stability of single-crystal lithium-ion cathodes at high voltage

Abstract: Single-crystal cathode materials for lithium-ion batteries have attracted increasing interest in providing greater capacity retention than their polycrystalline counterparts. However, after being cycled at high voltages, these single-crystal materials exhibit severe structural instability and capacity fade. Understanding how the surface structural changes determine the performance degradation over cycling is crucial, but remains elusive. Here, we investigate the correlation of the surface structure, internal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
207
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(211 citation statements)
references
References 50 publications
4
207
0
Order By: Relevance
“…The structure decay from layer structure (R‐m) to spinel (Fd‐m), and even to rock‐salt phase (Fm‐m) (the FFT pattern; the insets in Figure a) from the exterior to the interior of NCM accompanied with oxidative decomposition of electrolyte (Figure 10a), related to a high concentration of metastable Ni 4+ in NCM at full charged state, which may be reduced to the thermodynamically stable Ni 2+ upon extended cycling. [ 32,33 ] In the case of NCM‐2, the layer structure (R‐m) is well maintained (Figure 10b and Figure S11, Supporting Information), as the FFT patterns (insets in Figure 10b) with a highly crystalline structure. These results indicate that the structure of NCM is well protected by the passivation layer, inhibiting the side reaction during cycling.…”
Section: Resultsmentioning
confidence: 97%
“…The structure decay from layer structure (R‐m) to spinel (Fd‐m), and even to rock‐salt phase (Fm‐m) (the FFT pattern; the insets in Figure a) from the exterior to the interior of NCM accompanied with oxidative decomposition of electrolyte (Figure 10a), related to a high concentration of metastable Ni 4+ in NCM at full charged state, which may be reduced to the thermodynamically stable Ni 2+ upon extended cycling. [ 32,33 ] In the case of NCM‐2, the layer structure (R‐m) is well maintained (Figure 10b and Figure S11, Supporting Information), as the FFT patterns (insets in Figure 10b) with a highly crystalline structure. These results indicate that the structure of NCM is well protected by the passivation layer, inhibiting the side reaction during cycling.…”
Section: Resultsmentioning
confidence: 97%
“…For instance, it has been reported that through operational cycling, oxide materials may be susceptible to lattice-invariant shearing, resulting in irreversible structural changes. [12] Additionally, the release of transition metals via dissolution [13] as well as surface restructuring through the formation of other crystallographic phases [14,15] remains problematic. To understand structural issues further, X-ray techniques have proven highly useful in the characterization of NMC electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…[18,37,38,52] Moreover, very recently, our group demonstrated that commercial-grade LiNi 0.80 Co 0.10 Mn 0.10 O 2 , consisting of randomly oriented grains, was susceptible to severe disintegration of the secondary particles even at the initial charge and discharge due to the anisotropic volumetric strains, which led to poor electrochemical performance of low ICE and degradation of cycling retention. [37] In this regard, recently emerging research directions for cathodes in advanced LIBs based on LEs, the development of cracking-free single-crystalline Ni-rich layered oxides, [30,[53][54][55][56][57][58] could be in the same vein for the development of practical ASLBs.The recent discovery of halide SEs (Li 3 YX 6 (X = Cl, Br)) with Li + conductivities of over 10 −4 S cm −1 has opened new opportunities due to their excellent electrochemical oxidation stability (>4 V vs Li/Li + ) and much better chemical stability (more oxygen-resistant and no H 2 S evolution), compared to sulfide SEs, as well as deformability. [59,60] By exploration of the Li 3 YX 6 analogs, highly Li + conductive halide SEs of Li 3 InCl 6 (1.5 mS cm −1 ), [61] Li 3 ErCl 6 (0.33 mS cm −1 ), [62] Li 3 ScCl 6 (3.0 mS cm −1 ), [63,64] and Li 3−x M 1−x Zr x Cl 6 (M = Y, Er, 1.4 mS cm −1 ), [65] Li 2+x Zr 1−x Fe x Cl 6 (max.…”
mentioning
confidence: 99%
“…[18,37,38,52] Moreover, very recently, our group demonstrated that commercial-grade LiNi 0.80 Co 0.10 Mn 0.10 O 2 , consisting of randomly oriented grains, was susceptible to severe disintegration of the secondary particles even at the initial charge and discharge due to the anisotropic volumetric strains, which led to poor electrochemical performance of low ICE and degradation of cycling retention. [37] In this regard, recently emerging research directions for cathodes in advanced LIBs based on LEs, the development of cracking-free single-crystalline Ni-rich layered oxides, [30,[53][54][55][56][57][58] could be in the same vein for the development of practical ASLBs.…”
mentioning
confidence: 99%